2019
DOI: 10.1002/mbo3.870
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of urediospore morphology, histopathology and epidemiological components on wheat plants infected with UV‐B‐induced mutant strains of Puccinia striiformis f. sp. tritici

Abstract: Planting resistant cultivars is the most economical and effective measure to control wheat stripe rust caused by Puccinia striiformis f. sp. tritici (Pst), but the cultivars often lose their resistance due to the emergence of new physiological races. The UV‐B‐irradiated urediospores of the Pst physiological race CYR32 in China were inoculated on wheat cultivar Guinong 22 for screening virulence‐mutant strains. CYR32 and mutant strains (CYR32‐5 and CYR32‐61) before and after UV‐B radiation were used to conduct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In the previous study (Zhao et al, 2019), the urediospores of the Pst physiological race CYR32 were irradiated with UV-B radiation under a radiation dose (the radiation intensity was 250 µw/cm 2 , and the radiation time was 95 min) for which the relative lethal rate of urediospores was approximately 90% (i.e., the relative germination rate of urediospores was approximately 10%); then the irradiated urediospores were inoculated on the seedlings of Guinong 22 to screen virulence-mutant strains. Finally, two virulence-mutant strains named CYR32-5 and CYR32-61, with stable infection types on Guinong 22 throughout four successive generations, were obtained.…”
Section: Methodsmentioning
confidence: 86%
See 3 more Smart Citations
“…In the previous study (Zhao et al, 2019), the urediospores of the Pst physiological race CYR32 were irradiated with UV-B radiation under a radiation dose (the radiation intensity was 250 µw/cm 2 , and the radiation time was 95 min) for which the relative lethal rate of urediospores was approximately 90% (i.e., the relative germination rate of urediospores was approximately 10%); then the irradiated urediospores were inoculated on the seedlings of Guinong 22 to screen virulence-mutant strains. Finally, two virulence-mutant strains named CYR32-5 and CYR32-61, with stable infection types on Guinong 22 throughout four successive generations, were obtained.…”
Section: Methodsmentioning
confidence: 86%
“…It has been reported that UV-B radiation can induce virulence variation in Pst ( Shang et al, 1994 ; Huang et al, 2005 ; Wang et al, 2009 ; Zhao et al, 2019 ). Similarly, in studies on two other important pathogens— Puccinia triticina ( Neugebauer et al, 2018 ) and P .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the rust fungi, the early infection processes were well studied in hostpathogen combinations of wheat-P. striiformis f.sp. tritici (Ma and Shang, 2009, Wang et al, 2010, Zhang et al, 2012, Esmail et al, 2018, Zhao et al, 2019, wheat -P. triticina (Wang et al, 2012, Wesp-Guterres et al, 2013, wheat-P. graminis (Maree et al, 2020), barley -P. graminis (Maree et al, 2020), Coffee -Hemileia vastatrix (Ramiro et al, 2009), soybean -Phakopsora pachyrhizi (Vittal et al, 2014) and grapevine-Neophysopella tropicalis and N. meliosmae-myrianthae (Santos et al, 2020). However, such studies characterizing rust resistance in groundnut at cellular and tissue levels are limited.…”
Section: Introductionmentioning
confidence: 99%